Pengaruh Pemberian Pakan Sumber Energi terhadap Profil Darah Kambing Kacang Jantan - Joni Ordianus Bere; Stefanus Sio; Gerson Frans Bira (JAS, 2019)
This research was conducted in Nunmafo Village, Insana District, TTU Regency. The purpose of this study was to determine the effect of energy source feeding on the blood profile of male goat cattle. The purpose of this study was to determine the effect of energy source feeding on complete blood profile in male goat cattle. The treatments tested in this study consisted of R0 = 80% natural grass + 20% lamtoro. R1 = 50% natural grass + 20% lamtoro + 30% corn. R2 = 50% natural grass + 20% lamtoro + 30% rice bran. R3 = 50% natural grass + 20% lamtoro + 30% cassava. The results showed that the feeding of energy sources in male goats had no significant effect on blood glucose levels at 0, 4 and 6 hours but had a significant effect (P> 0.05) at 2 hours after being fed, whereas for hemoglobin, hematocrit levels, Plasma Total Protein has no real effect. Based on the results of this study it can be concluded that feeding different energy sources does not affect the blood profile of male goats in general but slightly affects blood glucose levels in taking 2 hours after being fed and total plasma protein 6 hours after being fed. An increase in blood levels from normal blood levels.